2005
DOI: 10.4049/jimmunol.174.10.5968
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Infusion of Syngeneic Apoptotic Cells by Photopheresis Induces Antigen-Specific Regulatory T Cells

Abstract: The basis of extracorporeal photopheresis is the reinfusion of leukocytes previously exposed to 8-methoxypsoralen (8-MOP) and UVA radiation. It has been approved for the palliative treatment of cutaneous T cell lymphoma and has reported benefits in autoimmune diseases, transplant rejection, and graft-vs-host disease. However, the underlying mechanism of photopheresis remains unresolved. Because UVB radiation can cause immune tolerance via induction of regulatory T cells, we studied whether photopheresis exerts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
201
3
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(220 citation statements)
references
References 65 publications
9
201
3
7
Order By: Relevance
“…[19][20][21] Notably, it has been shown that the immune response to a foreign antigen can also be suppressed by delivering it systemically in association with syngeneic ACs. [22][23][24] In this study, we demonstrate that infusion of apoptotic syngeneic fibroblasts modified to express a hFVIII transgene significantly inhibits the immune response against hFVIII in both naive and preimmunized hemophilic mice. Furthermore, we show that the hyporesponsiveness to hFVIII is associated with the generation of antigen-specific Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Notably, it has been shown that the immune response to a foreign antigen can also be suppressed by delivering it systemically in association with syngeneic ACs. [22][23][24] In this study, we demonstrate that infusion of apoptotic syngeneic fibroblasts modified to express a hFVIII transgene significantly inhibits the immune response against hFVIII in both naive and preimmunized hemophilic mice. Furthermore, we show that the hyporesponsiveness to hFVIII is associated with the generation of antigen-specific Tregs.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of caspase-3 and DNA ladder formation increases after UV-A irradiation leading to cellular death [25]. It was previously shown that intravenous injection of PUVA treated cells exerts silencing of the immune system by inducing regulatory T cells [19]. The anti-inflammatory cytokine IL-10 was identified as critical inhibitory component in the sensitization and effector phase of contact hypersensitivity [18].…”
Section: Discussionmentioning
confidence: 99%
“…This finding also underscores the possibility of utilizing a type of universal apoptotic cell, such as apoptotic PBMCs in clinics for inducing immune tolerance to the targeted antigens including self-antigens in autoimmune diseases and MHC antigens in allogeneic transplantations. Indeed, Maeda et al [11] reported that intravenous injection of apoptotic syngeneic splenocytes led to immune tolerance specific to DNFB antigens simultaneously administered to the skin during induction of contact hypersensitivity. Recent evidence has also shown that T1D patients benefited from photopheresis, which is proposed to be associated with photopheresis-induced apoptosis of blood cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to find alternative techniques in utilizing apoptotic cells to induce β cell antigen-specific T cell tolerance. Recently, it was reported that intravenous injection of apoptotic syngeneic splenocytes along with administration of a hapten, 2,4,dinitrofluorobenzene (DNFB) to the skin induced immune tolerance specific to DNFB [11]. This study suggests that it is possible to utilize apoptotic non-β cells, such as splenocytes or peripheral blood mononuclear cells to induce immune tolerance to β cell antigens with the exposure of endogenous β cell antigens during the process of autoimmunity, thereby preventing autoimmune diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation